La politique industrielle dans la Communauté économique européenne : Crise et changement - Courtis, Kenneth (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1981)
The ultimate goal of industrial policy is to allow constant improvement in both the quality and standard of living. Necessary conditions to such improvement are full employment at both high, real wages and at increasing rates of productivity. For the European Economic Community, productivity must not only increase absolutely but also relatively, in comparison to other international competitors. Yet during the 60's and early 70's, Europe's competitive position in a number of major industrial sectors weakened, such that the energy shock, when it did come, signaled a reversal in established terms of trade. Suddenly, the Common Market was confronted with new problems of adjustment and decline.It is within this context that both the role and the focus of EEC industrial policy have changea and that come to play the underlying dynamics that shape European industrial policy formulation. In these new economic conditions, traditional policies of demand management, of counter-cyclical measures and of monetary control have proved inadequate to restore real growth, full employment and ordered structural change. While purely national solutions appear to be no longer possible in many sectors, member countries have become increasingly locked into competitive rather than the complementary industrial strategies. New and intense political strains have emerged.Political legitimacy and a clear mandate are critical to the formulation and implementation of industrial policy. Although the essential economic logic of the Treaty of Rome is clear, its political dimensions are less evident. Indeed there is nothing in the Common Market treaty about industrial policy. Yet as the question of industrial development moves to the centre of political debate, the future evolution of the community will be increasingly linked to EC industrial policy. This article analyzes European industrial policy as we enter the 80's. It begins with an analysis of the economic realities and the social and political forces behind the changing focus of European industrial policy and examines briefly the context of industrial policy formulation at the European Community level. Subsequently it turns to the new sectoral pattern and emphasis of European industrial policy. Finally, the article evaluates the evolution of European industrial policy in the latter part of the 70s and considers emerging trends.